Toxic effects of antimony in plants: Reasons and remediation possibilities—A review and future prospects - Tang, Haiying; Meng, Guiyuan; Xiang, Junqing; Mahmood, Athar; Xiang, Guohong; SanaUllah,; Liu, Ying; Huang, Guoqin (Frontiers in Plant Science, 2022)
Antimony (Sb) is dangerous heavy metal (HM) that is posing serious threat to plants, animals and human health. The various sources including leaching from mining wastes, weathering of sulfide ores are major source of Sb introduction into our soils and aquatic environments. The crops grown on Sb contaminated soils are major reason of Sb entry into humans by eating Sb contaminated foods. Sb toxicity in plants reduces seed germination, root and shoot growth, and cause substantial reduction in plant growth and final productions. Moreover, Sb also induced chlorosis, cause damage to photosynthetic apparatus, reduce membrane stability and nutrient uptake and increase the oxidative stress by increasing reactive oxygen species thereby reduce plant growth and development. The threats induced by Sb toxicity and Sb concentration are soils is increasing day by day which would be major threat to crop production and human health. Additionally, lack of appropriate measures regarding the remediation of Sb contaminating soils will future intensified the current situation. Therefore, future research must be aimed to devise appropriate measures to mitigate the hazardous impacts of Sb toxicity on plants, humans and environment and to prevent the entry of Sb into our ecosystem. This review discussed the different sources of Sb entry into environment and toxic effects of Sb on humans, and plants. Moreover, we have also discussed the role of diverse strategies to remediate the Sb contaminated soils to prevent the entry of Sb into human food chain. Additionally, we also identified the various research gaps that must be addressed in future research programs. We believe that this review will help to readers to develop the appropriate measures to minimize the toxic effects of Sb and its entry into our ecosystem.